Adolescent development of inhibition as a function of SES and gender: Converging evidence from behavior and fMRI. Issue 8 (22nd May 2015) - Spielberg, Jeffrey M.; Galarce, Ezequiel M.; Ladouceur, Cecile D.; McMakin, Dana L.; Olino, Thomas M.; Forbes, Erika E.; Silk, Jennifer S.; Ryan, Neal D.; Dahl, Ronald E.
Abstract The ability to adaptively inhibit responses to tempting/distracting stimuli in the pursuit of goals is an essential set of skills necessary for adult competence and wellbeing. These inhibitory capacities develop throughout childhood, with growing evidence of important maturational changes occurring in adolescence. There also has been intense interest in the role of social adversity on the development of executive function, including inhibitory control. We hypothesized that the onset of adolescence could be a time of particular opportunity/vulnerability in the development of inhibition due to the large degree of maturational changes in neural systems involved in regulatory control. We investigated this hypothesis in a longitudinal study of adolescents by examining the impact of socioeconomic status (SES) on the maturation of inhibition and concurrent brain function. Furthermore, we examined gender as a potential moderator of this relationship, given evidence of gender‐specificity in the developmental pathways of inhibition as well as sex differences in adolescent development. Results reveal that lower SES is associated with worse behavioral inhibition over time and a concurrent increase in anterior cingulate (ACC) activation, but only in girls. We also found that lower SES girls exhibited decreased ACC ↔ dorsolateral prefrontal cortex (dlPFC) coupling over time. Our findings suggest that female adolescents with lower SES appear to develop less efficient inhibitory processing in dlPFC, requiring greater and relatively unsuccessful compensatory recruitment of ACC. In summary, the present study provides a novel window into the neural mechanisms by which the influence of SES on inhibition may be transmitted during adolescence. Hum Brain Mapp 36:3194–3203, 2015. © 2015 Wiley Periodicals, Inc.